Improvement of Interphase Stability of Hard Carbon for Sodium-Ion Battery by Ionic Liquid Additives - Dexi Meng; Zongkun Bian; Kailimai Su; Yan Wang; Zhibin Lu; Enlin Cai; Junwei Lang (Batteries)
Hard carbon (HC), which is one of the anode materials widely used in commercial sodium-ion batteries at present, suffers from a thick and unstable solid electrolyte interface (SEI) layer formed by the self-reduction in traditional carbonate-based electrolytes on its surface. This phenomenon impacts the battery’s Coulomb efficiency, cycle stability, and rate performance. In this paper, a pyrrolidinium-type di-cation ionic liquid, butyl-1,4-di(methylpyrrolidinium) di[hexafluorophosphate] (C4di[mPy].di[PF6]), is studied as an electrolyte additive to improve the interphase stability of the HC anode. The PF6− in C4di[mPy].di[PF6] enhances the coordination number between Na+ and PF6−, and C4di[mPy]2+ is preferentially reduced, jointly participating in the construction of stable, thin, dense and NaF-rich SEI films, thus laying the foundation for improving battery performance. As a result, in the carbonate electrolyte containing 2 wt% C4di[mPy].di[PF6], the reversible capacity of the HC/Na half-cell is increased by 14.7%, and the capacity retention rate remains at 90.4% after 400 cycles. This work provides reference for future research and design of high-performance ion liquid additives.